Kaempferol: A Dietary Flavonol in Alleviating Obesity - Nejabati, Hamid R.; Nikzad, Sadeneh; Roshangar, Leila (Current Pharmaceutical Design, 2023)
Obesity is considered as a chronic and high-prevalence disease on a global scale which affects all genders and ages. Although various drugs have been confirmed for the treatment of obesity, these medications have been shown to have a number of adverse effects on health. It is highlighted that natural products have an alleviative role in a broad spectrum of diseases, in particular obesity, and diabetes. Kaempferol (KMP), a plant- derived flavonol, is considerably engaged in the suppression of oxidative stress, radical scavenging, opposing cellular toxicity, and induction of the production and release of growth factors. This flavonol combats obesity by suppressing adipogenesis, regulating lipid and glucose metabolism, changing gut microbiota, and activating autophagy. Also, studies have shown that KMP exerts its anti-obesity actions by decreasing the accumulation of lipids and triglycerides (TGs), increasing fatty acid oxidation, and regulating multiple metabolic genes in the adipocytes. Considering that KMP may be a potential candidate for combating obesity, this paper summarizes the possible therapeutic roles of KMP in the treatment and prevention of this disease.
Keywords: Obesity